The depositional history of the Knysna estuary since European colonization in the context of sea level and human impacts - Kirsten, Kelly L.; Pretorius, Lauren; Meadows, Michael E.; Weij, Rieneke; Aquino-López, Marco; Antonopoulos, Helen G.; Dubazana, Yakhuluntu; Qadeer, Abdul; Finch, Jemma; Bao, Kunshan (Frontiers in Ecology and Evolution, 2023)
Introduction Estuaries are highly vulnerable systems and increasingly exposed to a number of environmental, climatic and human-induced stressors. The Knysna estuary and lagoon complex, on the south coast of South Africa, is regarded as environmentally and economically important, yet faces regional impacts resulting from ongoing urbanisation and land use change as well as the significant global threats of rising sea levels and changing climate. Although the estuary has been reasonably well studied in terms of modern ecological processes, little is known of how the system has responded to changes in the longer term, not least the impact of European colonization and subsequent population growth and economic development. Methods In order to address this shortcoming, a series of shallow (<1 m) cores was extracted from a range of representative habitats and marine influences in the estuary and three of these (namely KNY-19A, KNY-19B, KNY-19G) selected for detailed analysis, including organic matter content, magnetic susceptibility, selected elemental analysis and particle size. Results and Discussion Notwithstanding the challenges of dating estuarine sediments due to the possibility of erosion and resuspension, combined modelling of 210Pb and 14C ages is successfully deployed to develop an age-depth relationship for each core, providing a chronological framework for late Holocene environmental changes. Sedimentary characteristics of the three cores, taken in contrasting estuarine conditions, yield insights as to how different parts of the estuary responded to changes in sea level and anthropogenic activities in and around the Knysna basin, as well as in the wider catchment.